Slab for high-strength steel sheet, method for cooling same, method for producing high-strength hot-rolled steel sheet, method for producing high-strength cold-rolled steel sheet, and method for producing high-strength plated steel sheet

By controlling the microstructure structure and cooling method of the surface layer of the slab, the cracking problem during the cooling process of high alloy slabs is solved, and the stability of high-strength steel plates and the quality of finished products are improved, thereby reducing surface defects.

CN119173646APending Publication Date: 2024-12-20JFE STEEL CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380038868.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-09
Filing Date
2023-03-29
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The prior art is difficult to effectively suppress cracking problems during cooling of high alloy slabs, resulting in breakage of slabs during handling and processing, and surface defects occur after hot rolling.

Method used

By controlling the microstructure structure of the surface layer of the slab, we ensure that the average original austenite particle size is less than 2.0mm, the area ratio of bainite ferrite and tempered martensite is more than 50% or less than 97%, and the residual austenite is less than 10% or less than 100%. The area ratio is more than 3% and less than 30%, the ferrite area ratio is less than 20%, and a specific cooling and heating method is adopted, including the retention time of 1200°C or less than 1450°C or less than 130 seconds, and 700°C or more than 850°C or less. The cooling rate is 25°C/hr or above.

Benefits of technology

Effectively suppress cracking of slabs, reduce surface defects of steel plates after hot rolling, cold rolling or plated, and ensure the finished product quality of high-strength steel plates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005121587720000231
    Figure BDA0005121587720000231
  • Figure BDA0005121587720000241
    Figure BDA0005121587720000241
  • Figure BDA0005121587720000251
    Figure BDA0005121587720000251
Patent Text Reader

Abstract

Provided are: a slab for a high-strength steel sheet, which does not cause slab cracking during cooling of the slab; and a method for cooling the slab. Also provided are a method for producing a high-strength hot-rolled steel sheet, a high-strength cold-rolled steel sheet, and a high-strength plated steel sheet using the slab. A slab for a high-strength steel sheet, which is used for a continuous casting of a high-strength steel sheet, and which is characterized in that: the average original austenite particle size at a position 10 mm from the slab surface layer is 2.0 mm or less, and the total area ratio of bainitic ferrite and tempered martensite in the microstructure is 50-97%; the retained austenite is 3-30% in area ratio, the ferrite is 20% or less in area ratio, and the total of pearlite and quenched martensite is 20% or less in area ratio.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a high-strength steel plate slab which prevents cracking during cooling and a cooling method thereof, and also relates to a method for manufacturing a high-strength hot-rolled steel plate from the high-strength steel plate slab, a high-strength cold-rolled steel plate from the high-strength hot-rolled steel plate, and a high-strength plated steel plate from the high-strength cold-rolled steel plate. Background Art

[0002] In recent years, in the automotive field, in order to achieve both further thinning of the vehicle body and ensuring collision safety, the strength of high-strength steel has been further increased, and high alloying has been carried out for this purpose. The toughness of the slab has been greatly reduced by high alloying.

[0003] As the toughness decreases due to high alloying, cracks during slab cooling, so-called seasonal cracks, frequently occur. If seasonal cracks occur, the slab breaks during transportation and may not be available for hot rolling. In addition, even if the slab does not break, cracks will open during hot rolling and the hot-rolled steel sheet may break. Alternatively, for slabs with small cracks, they appear as surface defects such as scaly folding marks and streaks on the steel sheet after hot rolling, cold rolling, annealing or plating. Usually, cracks on the surface of the slab are removed by a grinder. However, due to the high alloying, the toughness of the slab is reduced, and the cracks develop due to the stress of the grinder, and sometimes they cannot be completely removed. On the other hand, for slabs with small cracks, they are sometimes overlooked and appear as surface defects in the steel sheet after hot rolling, cold rolling, annealing or plating. Based on the above situation, it is necessary to suppress seasonal cracks in the slab.

[0004] In this regard, for example, countermeasures for slab cracking as described in Patent Documents 1 and 2 have been studied. Patent Document 1 discloses a method of suppressing bainite / martensite transformation and reducing stress caused by the phase transformation expansion by slow cooling in the temperature range of 700 to 500°C for the phase transformation from austenite to ferrite. Patent Document 2 discloses a method of reducing the temperature difference and stress during phase transformation by starting slow cooling immediately after casting, performing slow cooling at a temperature of 700°C or higher for more than 10 hours, and further slow cooling to a temperature of 700 to 500°C.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2020-139209

[0008] Patent Document 2: Japanese Patent Application Publication No. 2019-167560 Summary of the invention

[0009] Problems to be solved by the invention

[0010] However, the conventional technology has the following problems.

[0011] The toughness of a slab with a higher alloy content is low, and the techniques of Patent Documents 1 and 2 have a problem in that seasonal cracking of the slab cannot be completely suppressed.

[0012] The present invention has been made in view of the above circumstances, and its object is to provide a slab for high-strength steel plate and a cooling method thereof, in which even a high-alloy slab with low toughness does not crack during cooling of the slab. Another object is to provide a method for manufacturing a high-strength hot-rolled steel plate, a high-strength cold-rolled steel plate, and a high-strength plated steel plate using the slab.

[0013] Means for solving problems

[0014] The inventors of the present application have repeatedly conducted in-depth research to achieve the above-mentioned purpose. By analyzing the fracture morphology of slab cracking, it is found that there is at least one fracture surface on the fracture surface, which is an intergranular fracture surface along the original austenite grain boundary and a transgranular fracture surface (cleavage fracture surface) that crosses the original austenite grain boundary. Further repeated research has obtained the following insights.

[0015] (1) By setting the average prior austenite grain size at a position 10 mm from the surface of the slab to 2.0 mm or less, it is possible to suppress intergranular fracture along the prior austenite grain boundaries.

[0016] (2) By making the microstructure at a position 10 mm away from the surface of the slab have a total area ratio of bainitic ferrite and / or tempered martensite of not less than 50% and not more than 97%, a total area ratio of retained austenite of not less than 3% and not more than 30%, a total area ratio of ferrite of not more than 20%, and a total area ratio of pearlite and quenched martensite of not more than 20%, it is possible to suppress transgranular fracture that crosses the original austenite grains.

[0017] (3) By suppressing slab cracking, surface defects of the steel sheet after hot rolling, cold rolling, annealing or plating can be suppressed.

[0018] The present invention has been completed through further studies based on the above findings.

[0019] That is, the main configuration of the present invention is as follows.

[0020] [1] A slab for high-strength steel plate, which is a continuously cast slab for high-strength steel plate, characterized in that the average original austenite grain size at a position 10 mm from the surface of the slab is less than 2.0 mm, and in the microstructure at a position 10 mm from the surface of the slab, the total area ratio of bainitic ferrite and tempered martensite is not less than 50% and not more than 97%, the area ratio of retained austenite is not less than 3% and not more than 30%, the area ratio of ferrite is not more than 20%, and the area ratio of pearlite and quenched martensite is not more than 20%.

[0021] [2] The slab for high-strength steel sheet as described in 1 above is characterized in that the slab for high-strength steel sheet has the following composition, which contains, in terms of mass%, C: 0.10% to 0.50%, Si: 0.10% to 2.50%, Mn: 1.00% to 5.00%, P: 0.100% to 0.100%, S: 0.0200% to 0.0200%, Al: 0.005% to 2.500%, N: 0.0100% to 0.0100%, and O: 0.0100% to 0.0100%, and further optionally contains Ti: 0.200% to 0.200%, Nb: 0.200% to 0.200%, V: 0.200% to 0.200%, Tg: 0.000% to 0.100%, and Zr: 0.000% to 0.100%. At least one element selected from a: less than 0.10%, W: less than 0.10%, B: less than 0.0100%, Cr: less than 1.00%, Mo: less than 1.00%, Co: less than 1.00%, Ni: less than 1.00%, Cu: less than 1.00%, Sn: less than 0.200%, Sb: less than 0.200%, Ca: less than 0.0100%, Mg: less than 0.0100%, REM: less than 0.0100%, Zr: less than 0.100%, Te: less than 0.100%, Hf: less than 0.10% and Bi: less than 0.200%, and the balance is Fe and unavoidable impurities.

[0022] [3] The slab for high-strength steel sheet according to item 1 above, wherein the slab for high-strength steel sheet has a composition comprising, in mass %, C: 0.10% to 0.50%, Si: 0.70% to 2.50%, Mn: 1.00% to 5.00%, P: 0.100% to 0.100%, S: 0.0200% to 0.0200%, Al: 0.005% to 2.500%, N: 0.0100% to 0.0100%, and O: 0.0100% to 0.0100%, and further optionally contains Ti: 0.200% to 0.200%, Nb: 0.200% to 0.200%, V: 0.200% to 0.200%, Ta: At least one element selected from the group consisting of: Cu: 0.0100% or less, W: 0.10% or less, B: 0.0100% or less, Cr: 1.00% or less, Mo: 1.00% or less, Co: 1.00% or less, Ni: 1.00% or less, Cu: 1.00% or less, Sn: 0.200% or less, Sb: 0.200% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, REM: 0.0100% or less, Zr: 0.100% or less, Te: 0.100% or less, Hf: 0.10% or less and Bi: 0.200% or less, and the balance being Fe and unavoidable impurities.

[0023] [4] A method for cooling a slab for a high-strength steel plate, characterized in that the slab for a high-strength steel plate having the composition described in 2 is cooled in such a manner that the residence time at a temperature of 1200°C to 1450°C at the center of the slab width and 10 mm below the surface is 130 seconds or less, and then cooled in such a manner that the average cooling rate when the surface temperature at the center of the slab width is 700°C to 850°C is 25°C / hr or more, and then cooled in such a manner that the average cooling rate when the surface temperature is 550°C to 700°C is 20°C / hr or more. The material is cooled in the above manner, and then cooled in a manner such that the average cooling rate at a temperature of 400°C to 550°C becomes 15°C / hr or more, and then cooled to a cooling stop temperature of 250°C to 400°C, and then heated to a reheating temperature higher than the aforementioned cooling stop temperature and below 450°C, and then cooled in a manner such that the average cooling rate at a temperature of 200°C to 200°C becomes 30°C / hr or less.

[0024] [5] A method for cooling a slab for high-strength steel plate, characterized in that the slab for high-strength steel plate having the composition described in 3 above is cooled in such a manner that the residence time at a temperature of 1200°C to 1450°C at the center of the slab width and 10 mm below the surface is 130 seconds or less, and then cooled in such a manner that the average cooling rate is 25°C / hr or more when the surface temperature at the center of the slab width is 700°C to 850°C, and then cooled in such a manner that the average cooling rate is 20°C / hr or more when the surface temperature is 550°C to 700°C, and then cooled in such a manner that the average cooling rate is 10°C / hr or more when the surface temperature is 400°C to 550°C, and then cooled in such a manner that the average cooling rate is 30°C / hr or less when the surface temperature is 200°C to 400°C.

[0025] [6] A method for manufacturing a high-strength hot-rolled steel sheet, characterized in that a slab for a high-strength steel sheet as described in any one of 1 to 3 above is heated in such a manner that the slab heating temperature is in the range of not less than 1000°C and not more than 1300°C, finish rolling is performed after rough rolling in such a manner that the finishing temperature of the finish rolling is not less than 750°C and not more than 1000°C, and coiling is performed in such a manner that the coiling temperature is not less than room temperature and not more than 750°C.

[0026] [7] A method for manufacturing a high-strength cold-rolled steel sheet, characterized in that the high-strength hot-rolled steel sheet manufactured by the manufacturing method described in 6 above is pickled, then cold-rolled in a manner such that the reduction ratio is 30% to 80%, and further optionally one of the following treatments is performed: a) the high-strength cold-rolled steel sheet obtained by the above-mentioned cold rolling is heated in a manner such that the annealing temperature is 750°C to 950°C, cooled to a cooling stop temperature of 300°C to 600°C, and then cooled to a temperature below 100°C; b) the high-strength cold-rolled steel sheet obtained by the above-mentioned cold rolling is heated to a temperature of 750°C to 950°C, cooled to a cooling stop temperature of 300°C to 600°C, and then cooled to a temperature below 100°C; The high-strength cold-rolled steel sheet obtained by the cold rolling is heated in a manner such that the annealing temperature becomes 750°C to 950°C, cooled to a cooling stop temperature of 130°C to 400°C, then reheated to 200°C to 450°C, and then cooled to 100°C or less; and c) the high-strength cold-rolled steel sheet obtained by the cold rolling is heated in a manner such that the annealing temperature becomes 750°C to 950°C, water quenching is started at 500°C or more, water-cooled to 100°C or less, and then reheated at 100°C to 300°C or more.

[0027] [8] A method for manufacturing a high-strength plated steel sheet, characterized in that the high-strength cold-rolled steel sheet obtained by the cold rolling described in the above 7 is heated in a manner such that the annealing temperature becomes 750°C to 950°C, and then the high-strength cold-rolled steel sheet is subjected to a molten metal plating treatment to form a plated steel sheet, and then the plated steel sheet is cooled under conditions where the cooling stop temperature is 150°C or less, and optionally, the molten metal plating treatment is set to one selected from zinc plating, zinc alloy plating, zinc-Al alloy plating and Al plating.

[0028] [9] The method for producing a high-strength plated steel sheet according to item 8, characterized in that the plated steel sheet subjected to the molten metal plating treatment is subjected to an alloying treatment.

[0029]

[10] A method for manufacturing a high-strength plated steel sheet, characterized in that the surface of the high-strength cold-rolled steel sheet manufactured using the manufacturing method described in 7 above is subjected to electroplating treatment, and optionally, the electroplating treatment is set to one selected from zinc plating, zinc alloy plating, zinc-Al alloy plating and Al plating.

[0030] Effects of the Invention

[0031] According to the present invention, a slab can be provided which does not crack during cooling even in a high-alloy high-strength steel sheet component system. In addition, a method for producing a high-strength hot-rolled steel sheet, a high-strength cold-rolled steel sheet, and a high-strength plated steel sheet with few surface defects using the slab can be provided. DETAILED DESCRIPTION

[0032] The following is a detailed description of the embodiments of the present invention. In addition, the following embodiments are examples of steel structures and methods for embodying the technical concept of the present invention, and their configurations are not limited to the following configurations. That is, the technical concept of the present invention can be modified in various ways within the technical scope described in the claims.

[0033] First, the appropriate range of the microstructure of the slab and the reasons for the limitation are described. In the following description, "%" indicating the microstructure composition ratio means "area %" unless otherwise specified.

[0034] [Average prior austenite grain size: 2.0 mm or less]

[0035] The average prior austenite grain size is a factor that determines the unit of fracture. The larger the grain size, the lower the toughness of the slab, and the slab cracking occurs along the intergranular fracture surface. In order to suppress the slab cracking, the average prior austenite grain size at a position 10 mm from the slab surface needs to be 2.0 mm or less. It is preferably 1.8 mm or less, and more preferably 1.5 mm or less. It should be noted that the average prior austenite grain size can be measured by the method described in the examples described later.

[0036] [Total area ratio of bainitic ferrite and tempered martensite: 50% or more and 97% or less]

[0037] As for bainitic ferrite and tempered martensite, which are important components in this embodiment, they have higher toughness than pearlite and quenched martensite, can make the toughness of steel higher, and can suppress slab cracking. In order to obtain this effect, it is necessary to make the total area ratio of bainitic ferrite and tempered martensite at a position 10mm from the surface of the slab be 50% or more. It is preferably 60% or more, more preferably 70% or more, and further preferably 80% or more. If it is greater than 97%, it is possible that the toughness improvement effect brought by the retained austenite cannot be obtained, and it is set to be less than 97%. It should be noted that the area ratio of bainitic ferrite and tempered martensite can be measured by the method described in the embodiments described later.

[0038] [Area ratio of retained austenite: 3% or more and 30% or less]

[0039] As for the retained austenite, which is an extremely important component in the present embodiment, its crystal structure is a face-centered cubic lattice (FCC). Since there is no cleavage plane, the toughness of the steel can be improved dramatically. In addition, if the retained austenite is subjected to high stress, martensitic transformation occurs. Even if cracks caused by slab cracking occur, martensite is generated in the stress concentration part at the front end of the crack, so that the stress concentration is alleviated and the development of the crack can be prevented. Therefore, the surface defects of the steel plate after hot rolling, cold rolling, annealing or plating can be suppressed. In order to obtain the above-mentioned effect, it is necessary to make the area ratio of the retained austenite at a position of 10mm from the surface of the slab 3% or more. Preferably, it is 5% or more, and more preferably 7% or more. If the retained austenite is greater than 30%, the unstable retained austenite increases, and it is possible to undergo martensitic transformation under small stress and reduce the toughness, so it is made less than 30%. It is preferably less than 25%, and more preferably less than 20%. In addition, the area ratio of retained austenite can be measured by the method described in Examples below.

[0040] [Area ratio of ferrite: 20% or less]

[0041] Compared with bainitic ferrite, tempered martensite, quenched martensite, retained austenite, and pearlite, ferrite has a larger grain size and lower strength. Therefore, when stress is applied, stress concentration occurs in ferrite, and cracking sometimes occurs starting from ferrite. In order to suppress the above-mentioned cracking, it is necessary to make the area ratio of ferrite at a position 10 mm from the surface of the slab 20% or less. It is preferably 15% or less, more preferably 10% or less, and further preferably 0%. It should be noted that the area ratio of ferrite can be measured by the method described in the examples described later.

[0042] [Total area ratio of pearlite and quenched martensite: 20% or less]

[0043] Compared with retained austenite, bainitic ferrite, and tempered martensite, pearlite and quenched martensite have poor toughness. If they exist in large quantities, cracking may sometimes occur starting from these structures. In order to suppress such cracking, the total area ratio of pearlite and quenched martensite at a position 10 mm from the surface of the slab needs to be 20% or less. It is preferably 15% or less, more preferably 10% or less, and even more preferably 0%. It should be noted that the area ratio of pearlite and quenched martensite can be measured by the method described in the examples described later.

[0044] Next, the appropriate range of the chemical composition and the reasons for its limitation will be described. In the following description, "%" indicating the content of the component elements of the steel means "mass %" unless otherwise specified.

[0045] [C: 0.10% or more and 0.50% or less]

[0046] C affects the residual austenite fraction of the slab and is an important element for improving the strength of the steel plate. When the C content is less than 0.10%, it may not be possible to ensure sufficient residual austenite in the slab. Or it may become difficult to achieve the tensile strength (TS) required for the steel plate. On the other hand, if the C content is greater than 0.50%, the quenched martensite fraction of the slab may become excessive. Therefore, the C content is preferably greater than 0.10% and less than 0.50%. More preferably, it is greater than 0.12%. More preferably, it is less than 0.45%. More preferably, it is greater than 0.15%. More preferably, it is less than 0.40%.

[0047] [Si: 0.10% to 2.50% or 0.70% to 2.50%]

[0048] Si suppresses the formation of carbides during slab cooling and promotes the formation of retained austenite, and is therefore an element that affects the fraction of retained austenite.

[0049] When the cooling method of the slab described later is accompanied by reheating, the Si content is preferably 0.10% or more. When the Si content is less than 0.10%, the fraction of retained austenite decreases, and slab cracking may occur. It is more preferably 0.15% or more. It is further preferably 0.20% or more.

[0050] In the case where the temperature of the slab is uniformly lowered without reheating in the cooling method described later, the Si content is preferably 0.70% or more. When the Si content is less than 0.70%, the fraction of retained austenite decreases, and slab cracking may occur. It is more preferably 0.90% or more. It is further preferably 1.00% or more.

[0051] On the other hand, if the Si content exceeds 2.50%, a strong scale is formed on the hot-rolled steel sheet, and surface defects may occur. Therefore, the Si content is preferably 2.50% or less, more preferably 2.00% or less, and further preferably 1.80% or less.

[0052] [Mn: 1.00% or more and 5.00% or less]

[0053] Mn affects the fraction of retained austenite and is an important element for improving the strength of steel plates. When the content of Mn is less than 1.00%, it may not be possible to ensure sufficient retained austenite in the slab. Or it may become difficult to achieve the tensile strength (TS) required for the steel plate. On the other hand, if the content of Mn is greater than 5.00%, the quenched martensite fraction of the slab may become excessive. Therefore, the content of Mn is preferably greater than 1.00% and less than 5.00%. More preferably, it is greater than 1.20%. More preferably, it is less than 4.50%. More preferably, it is greater than 1.40%. More preferably, it is less than 4.00%.

[0054] [P: 0.100% or less]

[0055] P segregates at the prior austenite grain boundary and makes the grain boundary embrittled, which may cause slab cracking. Therefore, the P content is preferably 0.100% or less. It should be noted that there is no particular lower limit for the P content, but P is a solid solution strengthening element that can increase the strength of the steel plate, so it is more preferably 0.001% or more. More preferably, it is 0.070% or less.

[0056] [S: 0.0200% or less]

[0057] S exists as a sulfide and is an element that causes slab embrittlement. Therefore, the S content is preferably 0.0200% or less. It should be noted that the lower limit of the S content is not particularly specified, but due to production technology constraints, it is more preferably 0.0001% or more. More preferably, it is 0.0050% or less.

[0058] [Al: 0.005% or more and 2.500% or less]

[0059] Al inhibits the formation of carbides during slab cooling and promotes the formation of retained austenite, so it is an element that affects the fraction of retained austenite in the slab. In addition, for deoxidation, it is preferably added at 0.005% or more. On the other hand, if the Al content is greater than 2.500%, it may cause slab embrittlement. Therefore, the Al content is preferably 0.005% or more and 2.500% or less. More preferably, it is 0.010% or more. More preferably, it is 1.000% or less. More preferably, it is 0.100% or less.

[0060] [N: 0.0100% or less]

[0061] N exists as a nitride and is an element that causes slab embrittlement. Therefore, the N content is preferably 0.0100% or less. It should be noted that there is no particular lower limit for the N content, but due to production technology constraints, the N content is more preferably 0.0001% or more. More preferably, it is 0.0050% or less.

[0062] [O: 0.0100% or less]

[0063] O exists as an oxide and is an element that causes slab embrittlement. Therefore, the content of O is preferably 0.0100% or less. It should be noted that there is no particular lower limit for the content of O, but due to production technology constraints, the content of O is more preferably 0.0001% or more. More preferably, it is 0.0050% or less.

[0064] The slab for high-strength steel sheet according to one embodiment of the present invention preferably has a composition containing the above-mentioned components, and the balance includes Fe and inevitable impurities. In addition, the slab for high-strength steel sheet according to one embodiment of the present invention preferably has a composition containing the above-mentioned components, and the balance is Fe and inevitable impurities. Here, as inevitable impurities, Zn, Pb and As can be mentioned. These impurities are allowed to be contained in a total of 0.100% or less.

[0065] The high-strength steel sheet of the present invention may contain, in addition to the above-mentioned component composition, at least one element selected from Ti: 0.200% or less, Nb: 0.200% or less, V: 0.200% or less, Ta: 0.10% or less, W: 0.10% or less, B: 0.0100% or less, Cr: 1.00% or less, Mo: 1.00% or less, Ni: 1.00% or less, Co: 1.00% or less, Cu: 1.00% or less, Sn: 0.200% or less, Sb: 0.200% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, REM: 0.0100% or less, Zr: 0.100% or less, Te: 0.100% or less, Hf: 0.10% or less, and Bi: 0.200% or less, alone or in combination.

[0066] If the contents of Ti, Nb and V are respectively less than 0.200%, coarse precipitates and inclusions will not be generated in large quantities, and the toughness of the slab will not be reduced. Therefore, the contents of Ti, Nb and V are preferably less than 0.200%. It should be noted that the lower limits of the contents of Ti, Nb and V are not particularly specified, but since fine carbides, nitrides or carbonitrides are formed during hot rolling or continuous annealing, the strength of the steel sheet is increased, so the contents of Ti, Nb and V are more preferably more than 0.001%. Therefore, when Ti, Nb and V are contained, their contents are respectively less than 0.200%. More preferably, they are more than 0.001%. More preferably, they are less than 0.100%.

[0067] If the contents of Ta and W are respectively less than 0.10%, coarse precipitates and inclusions will not be generated in large quantities, and the toughness of the slab will not be reduced. Therefore, the contents of Ta and W are preferably less than 0.10%. It should be noted that the lower limits of the contents of Ta and W are not particularly specified, but since fine carbides, nitrides or carbonitrides are formed during hot rolling or continuous annealing, the strength of the steel sheet is increased, so the contents of Ta and W are more preferably more than 0.01%. Therefore, when Ta and W are contained, their contents are respectively less than 0.10%. More preferably, they are more than 0.01%. More preferably, they are less than 0.08%.

[0068] If B is 0.0100% or less, the toughness of the slab will not be affected. Therefore, the content of B is preferably 0.0100% or less. It should be noted that the lower limit of the content of B is not particularly specified, but since B segregates at the austenite grain boundary during hot rolling and annealing and is an element that improves hardenability, the content of B is more preferably 0.0003% or more. Therefore, when B is contained, its content is 0.0100% or less. More preferably, it is 0.0003% or more. More preferably, it is 0.0080% or less.

[0069] If Cr, Mo and Ni are respectively less than 1.00%, coarse precipitates and inclusions will not increase, and the toughness of the slab will not be reduced. Therefore, the contents of Cr, Mo and Ni are preferably less than 1.00%. It should be noted that there is no particular lower limit for the contents of Cr, Mo and Ni, but since they are elements that improve hardenability, the contents of Cr, Mo and Ni are more preferably more than 0.01%. Therefore, when Cr, Mo and Ni are contained, their contents are respectively less than 1.00%. More preferably, they are more than 0.01%. More preferably, they are less than 0.80%.

[0070] If Co is 1.00% or less, coarse precipitates and inclusions will not increase, and the toughness of the slab will not be reduced. Therefore, the content of Co is preferably 1.00% or less. It should be noted that there is no particular lower limit for the content of Co, but since it is an element that improves hardenability, the content of Co is more preferably 0.001% or more. Therefore, when Co is contained, its content is 1.00% or less. More preferably, it is 0.001% or more. More preferably, it is 0.80% or less.

[0071] If Cu is less than 1.00%, coarse precipitates and inclusions will not increase, and the toughness of the slab will not be reduced. Therefore, the Cu content is preferably less than 1.00%. It should be noted that there is no particular lower limit for the Cu content, but since it is an element that improves hardenability, the Cu content is more preferably 0.01% or more. Therefore, when Cu is contained, its content is less than 1.00%. More preferably, it is more than 0.01%. More preferably, it is less than 0.80%.

[0072] If Sn is 0.200% or less, the toughness of the slab will not be affected. Therefore, the content of Sn is preferably 0.200% or less. It should be noted that the lower limit of the content of Sn is not particularly specified, but since Sn is an element that improves hardenability, the content of Sn is more preferably 0.001% or more. Therefore, when Sn is contained, its content is 0.200% or less. More preferably, it is 0.001% or more. More preferably, it is 0.100% or less.

[0073] If Sb is 0.200% or less, coarse precipitates and inclusions will not increase, and the toughness of the slab will not be reduced. Therefore, the Sb content is preferably 0.200% or less. It should be noted that there is no particular lower limit for the Sb content, but since it is an element that suppresses decarburization and can adjust the strength of the steel sheet, the Sb content is more preferably 0.001% or more. Therefore, when Sb is contained, its content is 0.200% or less. More preferably, it is 0.001% or more. More preferably, it is 0.100% or less.

[0074] If Ca, Mg and REM are 0.0100% or less, respectively, coarse precipitates and inclusions will not increase, and the toughness of the slab will not be reduced. Therefore, the content of Ca, Mg and REM is preferably 0.0100% or less. It should be noted that the lower limit of the content of Ca, Mg and REM is not particularly specified, but since they are elements that spheroidize the shape of nitrides and sulfides and improve the toughness of the slab, the content of Ca, Mg and REM is more preferably 0.0005% or more. Therefore, when Ca, Mg and REM are contained, their contents are 0.0100% or less. More preferably, they are 0.0005% or more. More preferably, they are 0.0050% or less.

[0075] If Zr and Te are respectively less than 0.100%, coarse precipitates and inclusions will not increase, and the toughness of the slab will not be reduced. Therefore, the content of Zr and Te is preferably less than 0.100%. It should be noted that there is no particular lower limit for the content of Zr and Te, but since they are elements that spheroidize the shape of nitrides and sulfides and improve the toughness of the slab, the content of Zr and Te is more preferably more than 0.001%. Therefore, when Zr and Te are contained, their contents are respectively less than 0.100%. More preferably, they are more than 0.001%. More preferably, they are less than 0.080%.

[0076] If Hf is 0.10% or less, coarse precipitates and inclusions will not increase, and the toughness of the slab will not be reduced. Therefore, the Hf content is preferably 0.10% or less. It should be noted that there is no particular lower limit for the Hf content, but since it is an element that spheroidizes the shape of nitrides and sulfides and improves the ultimate deformation capacity of the steel sheet, the Hf content is more preferably 0.01% or more. Therefore, when Hf is contained, its content is 0.10% or less. More preferably, it is 0.01% or more. More preferably, it is 0.08% or less.

[0077] If Bi is 0.200% or less, coarse precipitates and inclusions will not increase, and the toughness of the slab will not be reduced. Therefore, the Bi content is preferably 0.200% or less. It should be noted that there is no particular lower limit for the Bi content, but since it is an element that reduces segregation, the Bi content is more preferably 0.001% or more. Therefore, when Bi is contained, its content is 0.200% or less. More preferably, it is 0.001% or more. More preferably, it is 0.100% or less.

[0078] It should be noted that, for the above-mentioned Ti, Nb, V, Ta, W, B, Cr, Mo, Ni, Co, Cu, Sn, Sb, Ca, Mg, REM, Zr, Te, Hf and Bi, when the content is less than the preferred lower limit, the effect of the present invention is not impaired, and therefore they are contained as unavoidable impurities.

[0079] <Cooling Method for High-Strength Steel Plate Slab According to First Embodiment>

[0080] Next, a preferred method for cooling a slab to achieve the above-mentioned microstructure is described. The cooling method for a slab for high-strength steel plate according to the first embodiment is accompanied by reheating during cooling. Among the above-mentioned component compositions, a case where the cooling of the slab is accompanied by reheating is selected, and a steel raw material having the component composition is melted to manufacture a steel slab. In this embodiment, the melting method of the steel raw material is not particularly limited, and known melting methods such as a converter and an electric furnace are suitable. In addition, in order to prevent macrosegregation, the steel slab (slab) is preferably manufactured by a continuous casting method, but it can also be manufactured by a thin slab casting method, etc.

[0081] [Retention time at 1200°C to 1450°C from the end of casting at the center of the slab width and 10 mm below the surface: 130 seconds or less]

[0082] The original austenite grain size is a factor that determines the unit of fracture. The larger the grain size, the lower the toughness. The factor that determines the austenite grain size is the residence time above 1200°C and below 1450°C. The longer the residence time, the coarser the original austenite grain size. If the residence time above 1200°C and below 1450°C exceeds 130s, the average original austenite grain size is sometimes greater than 2.0mm, and slab cracking may occur. Therefore, the residence time above 1200°C and below 1450°C is 130s or less. Preferably, it is 120s or less. More preferably, it is 110s or less. More preferably, it is 100s or less. It should be noted that the lower limit of the residence time above 1200°C and below 1450°C is not specifically specified, but if the residence time is too short, the risk of breakout in continuous casting caused by uneven solidification becomes high, so it is made to be 40s or more. More preferably, it is 50s or more. Since the above temperature is difficult to measure, the temperature history at a position 10 mm below the surface of the slab is calculated by thermal conductivity analysis. The analysis position is the center of the slab width where the residence time of the above temperature range inside the slab is the longest.

[0083] [Average cooling rate when the surface temperature at the center of the slab width is 700°C or more and 850°C or less: 25°C / hr (°C / hour) or more]

[0084] The temperature range in which ferrite transformation occurs is from 700°C to 850°C. If the cooling rate in this temperature range is low, the area ratio of ferrite in the slab increases and the toughness of the slab decreases. In order to control the area ratio of ferrite to be lower, it is necessary to increase the cooling rate. In order to obtain such an effect, the average cooling rate at 700°C to 850°C is above 25°C / hr. It is preferably above 30°C / hr, more preferably above 40°C / hr, and further preferably above 50°C / hr. There is no particular upper limit on the average cooling rate, but since it is difficult to control the cooling stop at 250°C to 400°C, it is set to 1000°C / hr or less. It is preferably below 500°C / hr, more preferably below 200°C / hr. The cooling rate is measured using a thermocouple. After the slab comes out of the continuous casting machine, a thermocouple is set in the central part of the upper surface of the wide side (long side) of the slab and measured, and the cooling rate is obtained from the measured temperature. All the cooling rates of the slab described below are cooling rates obtained by the above-mentioned method.

[0085] [Average cooling rate at 550°C or higher and lower than 700°C: 20°C / hr or higher]

[0086] The temperature range of 550°C and below 700°C is the temperature range in which ferrite transformation and pearlite transformation occur. If the cooling rate in this temperature range is low, the ferrite and / or pearlite fraction of the slab increases, and the toughness of the slab decreases. Therefore, the average cooling rate at 550°C and below 700°C is set to 20°C / hr or more. It is preferably 30°C / hr or more, more preferably 40°C / hr or more, and further preferably 50°C / hr or more. There is no particular upper limit on the average cooling rate, but since it is difficult to control the cooling stop at 250°C and below 400°C, it is set to 1000°C / hr or less. It is preferably 500°C / hr or less, and more preferably 200°C / hr or less.

[0087] [Average cooling rate at 400°C or higher and lower than 550°C: 15°C / hr or higher]

[0088] The temperature range of 400°C or more and less than 550°C is the temperature range in which pearlite transformation and bainite transformation occur. If the cooling rate in this temperature range is low, the pearlite fraction of the slab becomes high and the toughness of the slab decreases. Therefore, the average cooling rate at 400°C or more and less than 550°C is set to 15°C / hr or more. It is preferably 20°C / hr or more, more preferably 30°C / hr or more, and further preferably 50°C / hr or more. There is no particular upper limit on the average cooling rate, but since it is difficult to control the cooling stop at 250°C or more and less than 400°C, it is set to 500°C / hr or less. It is preferably 300°C / hr or less, and more preferably 100°C / hr or less.

[0089] [Average cooling rate to cooling stop temperature of 250°C or higher and lower than 400°C: 10°C / hr or higher]

[0090] The temperature range of 250°C or more and less than 400°C is the temperature range in which bainite transformation and martensite transformation occur. In order to enrich carbon in untransformed austenite and generate retained austenite by reheating, it is necessary to leave untransformed austenite without completing the transformation during cooling to the cooling stop temperature. Therefore, the cooling rate to the cooling stop temperature is 10°C / hr or more. Preferably, it is 15°C / hr or more, more preferably 20°C / hr or more, and further preferably 30°C / hr or more. There is no particular upper limit on the average cooling rate, but since the control of the cooling stop temperature becomes difficult, it is set to 500°C / hr or less. Preferably, it is 300°C / hr or less, and more preferably 100°C / hr or less. In addition, if the cooling stop temperature is lower than 250°C, the transformation will be completed and retained austenite cannot be ensured. Therefore, the cooling stop temperature is set to 250°C or more. Preferably, it is 270°C or more, and more preferably, it is 300°C or more. If the cooling stop temperature reaches 400° C. or higher, pearlite transformation proceeds and retained austenite cannot be secured. Therefore, the cooling stop temperature is set to be lower than 400° C., preferably 380° C. or lower, and more preferably 350° C. or lower.

[0091] [Heating to a reheating temperature higher than the cooling stop temperature and 450° C. or lower]

[0092] By reheating from the cooling stop temperature, bainite transformation is promoted. When bainitic ferrite is generated, carbon is enriched in the untransformed austenite, which promotes the formation of retained austenite. In addition, in the case where martensitic transformation occurs until cooling stops, carbon is distributed and enriched from martensite to untransformed austenite by reheating, which promotes the formation of retained austenite. Below the cooling stop temperature, the enrichment of carbon to the untransformed austenite becomes insufficient, and the retained austenite cannot be ensured. Therefore, the reheating temperature is higher than the cooling stop temperature. Preferably, it is above the cooling stop temperature + 20 ° C, and more preferably, it is above the cooling stop temperature + 40 ° C. If the reheating temperature is higher than 450 ° C, the decomposition of the untransformed austenite occurs, and the retained austenite cannot be ensured. Therefore, the reheating temperature is below 450 ° C. Preferably, it is below 430 ° C, and more preferably, it is below 410 ° C.

[0093] [Average cooling rate at 200°C or higher and below reheating temperature is 30°C / hr or less]

[0094] The temperature range below the reheating temperature of 200°C is the temperature range in which bainite transformation and martensite transformation occur, and bainite transformation occurs at a temperature higher than martensite transformation. If the cooling rate within this temperature range is high, quenched martensite is generated, and the toughness of the slab is reduced. In addition, during the bainite transformation, when bainitic ferrite is generated, carbon is enriched in the untransformed austenite, promoting the formation of retained austenite. In order to ensure the residual austenite fraction and bainite fraction of the slab, sufficient time is required for the bainite transformation to occur. In addition, in the case of martensite transformation until the aforementioned cooling stops, carbon is distributed and enriched from martensite to untransformed austenite, promoting the formation of retained austenite. Therefore, the average cooling rate below the reheating temperature of 200°C is 30°C / hr or less. Preferably, it is 25°C / hr or less, and more preferably 20°C / hr or less. The lower limit of the average cooling rate is not particularly specified, but from the perspective of productivity, it is preferably 5°C / hr or more.

[0095] <Cooling Method for High-Strength Steel Plate Slab According to Second Embodiment>

[0096] The cooling method for a high-strength steel plate according to the second embodiment is that the temperature is uniformly lowered without reheating during cooling. The common parts with the first embodiment are omitted, and the different parts are described. Among the above-mentioned component compositions, the case where the slab is not reheated during cooling is selected, and a steel raw material having this component composition is melted to manufacture a steel slab in the same manner as the first embodiment.

[0097] [The residence time at 1200°C to 1450°C at the center of the slab width and 10 mm below the surface is 130 seconds or less]

[0098] This is the same as the first embodiment.

[0099] [Average cooling rate when the surface temperature at the center of the slab width is 700°C or higher and 850°C or lower: 25°C / hr or higher]

[0100] This is the same as the first embodiment.

[0101] [The average cooling rate at 550°C or higher and lower than 700°C is 20°C / hr or higher]

[0102] This is the same as the first embodiment.

[0103] [The average cooling rate at 400°C or higher and lower than 550°C is 10°C / hr or higher]

[0104] The temperature range of 400°C or more and less than 550°C is the temperature range in which pearlite transformation and bainite transformation occur. If the cooling rate in this temperature range is low, the pearlite fraction of the slab becomes high and the toughness of the slab decreases. Therefore, the average cooling rate at 400°C or more and less than 550°C is set to 10°C / hr or more. It is preferably 15°C / hr or more, more preferably 20°C / hr or more, and further preferably 30°C / hr or more. There is no particular upper limit on the average cooling rate, but since it is difficult to control the cooling rate at 200°C or more and less than 400°C, it is set to 500°C / hr or less. It is preferably 300°C / hr or less, and more preferably 100°C / hr or less.

[0105] [The average cooling rate at 200°C or higher and lower than 400°C is 30°C / hr or lower]

[0106] The temperature range of 200°C or more and less than 400°C is the temperature range in which bainite transformation and martensite transformation occur, and bainite transformation occurs at a higher temperature than martensite transformation. If the cooling rate within this temperature range is high, quenched martensite is generated, and the toughness of the slab is reduced. In addition, during the bainite transformation, when bainitic ferrite is generated, carbon is enriched in the untransformed austenite, promoting the formation of retained austenite. In order to ensure the residual austenite fraction and bainite fraction of the slab, sufficient time is required for the bainite transformation to occur. Therefore, the average cooling rate at 200°C or more and less than 400°C is 30°C / hr or less. Preferably, it is 25°C / hr or less, and more preferably, it is 20°C / hr or less. The lower limit of the average cooling rate is not particularly specified, but from the perspective of productivity, it is preferably 5°C / hr or more.

[0107] <Method for producing high-strength steel sheet>

[0108] According to the slab for high-strength steel sheet of the above embodiment, the slab does not crack after continuous casting, and the steel sheet after hot rolling, cold rolling, annealing or plating does not have surface defects such as scale folding marks and streaks, and high-strength hot-rolled steel sheet, high-strength cold-rolled steel sheet, and high-strength plated steel sheet can be manufactured. The manufacturing methods thereof are as follows.

[0109] First, any of the above-mentioned slabs for high-strength steel sheets is used. In the high-strength hot-rolled steel sheet, the slab is heated at a heating temperature in the range of 1000°C to 1300°C. After rough rolling, the finish rolling is performed at a finish rolling end temperature of 750°C to 1000°C, and the coiling is performed at a coiling temperature of 750°C to 750°C. Rapid cooling, plate temperature maintenance and heat preservation, and air cooling can be performed from the completion of the finish rolling to the coiling. After coiling, rolling can be performed at an elongation of 0.05% to 1.00%. In addition, pickling can also be performed. Pickling can be performed once or in multiple times. In this way, a high-strength hot-rolled steel sheet is manufactured.

[0110] In the case of high-strength cold-rolled steel sheet, the aforementioned high-strength hot-rolled steel sheet is used, and after pickling, cold rolling with a reduction rate of 30% or more and 80% or less is performed. Pickling can remove oxides on the surface of the steel sheet, so it is important to ensure the good chemical conversion treatment and plating quality of the high-strength steel sheet of the final product. In addition, pickling can be once or divided into multiple times. For cold rolling, since strain can be introduced uniformly and efficiently to obtain a uniform structure, it is preferably cold rolled by multi-pass rolling such as tandem multi-stand rolling or reverse rolling that requires more than 2 passes. Thus, the high-strength cold-rolled steel sheet 1 is manufactured.

[0111] The high-strength cold-rolled steel sheet 1 is heated at an annealing temperature of 750° C. to 950° C., cooled to a cooling stop temperature of 300° C. to 600° C., and then cooled to 100° C. or less. After the cooling, the high-strength cold-rolled steel sheet 2 can be manufactured by rolling at an elongation of 0.05% to 1.00%.

[0112] The high-strength cold-rolled steel sheet 1 is heated at an annealing temperature of 750°C to 950°C, cooled to a cooling stop temperature of 130°C to 400°C, then reheated to 200°C to 450°C, and then cooled to 100°C or less. After the cooling, the high-strength cold-rolled steel sheet 3 can be manufactured by rolling at an elongation of 0.05% to 1.00%.

[0113] The high-strength cold-rolled steel sheet 1 is heated at an annealing temperature of 750°C to 950°C, water quenched at 500°C to 100°C, and then reheated at 100°C to 300°C. After the reheating, the high-strength cold-rolled steel sheet 4 is manufactured by rolling at an elongation of 0.05% to 1.00%.

[0114] The high-strength cold-rolled steel sheet 1 is used and heated at an annealing temperature of 750°C to 950°C. Next, the high-strength cold-rolled steel sheet is subjected to a molten metal plating treatment to form a plated steel sheet. Next, the plated steel sheet is cooled under the condition that the cooling stop temperature is 150°C or less. In the molten metal plating treatment, for example, the cold-rolled steel sheet is immersed in a molten zinc plating bath at a temperature of 440°C to 500°C. In addition, it is preferred to use a molten zinc plating bath having an Al content of 0.10% to 0.23% by mass and the remainder being Zn and unavoidable impurities. In addition, the coating adhesion is preferably 20 to 80 g / m2 per side. 2 (Both sides are plated). It should be noted that the amount of coating can be adjusted by gas purging after the molten zinc plating process. It is also possible to roll at an elongation of 0.05% to 1.00% after the aforementioned cooling. In this way, a high-strength molten zinc plated steel sheet is manufactured. In addition to zinc plating, zinc alloy plating, zinc-Al alloy plating, Al plating, etc. can also be applied.

[0115] After the hot metal plating treatment, the plated steel sheet is subjected to an alloying treatment. For example, in the case of hot zinc plating, the alloying treatment is preferably performed at a temperature range of 460° C. to 600° C. Thus, a high-strength alloyed hot zinc plated steel sheet is manufactured.

[0116] High-strength plated steel sheets are produced by applying electroplating treatment to the surfaces of the high-strength cold-rolled steel sheets 1 to 4. As electroplating, zinc alloy plating, zinc-Al alloy plating, Al plating, etc. can be applied in addition to zinc plating.

[0117] The production conditions other than those described above are not particularly limited and may be prepared according to conventional methods.

[0118] Example

[0119] [Determination of average prior austenite grain size]

[0120] Here, the method for determining the average original austenite grain size is as follows. Cut a sample from the width center of the cooled slab, and use the slab thickness section parallel to the slab width direction as the observation surface. Next, mirror polish the observation surface using diamond paste, then fine polish using colloidal silica, and then etch with 3 vol.% (volume %) nitric acid ethanol solution to make the structure appear on the observation surface. Using an optical microscope, 5 fields of view were observed at a magnification of 10 times at a position 10 mm below the surface of the slab to obtain a tissue image. For the obtained tissue image, the original austenite grain size of the 5 fields of view was obtained using the cutting method according to JIS G 0551:2020, and these values ​​were averaged to obtain the average original austenite grain size.

[0121] [Method for measuring the area ratio of ferrite]

[0122] For the determination method of the ferrite area ratio, the observation surface of the slab is prepared in the same manner as the determination method of the above-mentioned average original austenite grain size. Next, the observation surface is mirror-polished using diamond paste, and then fine-polished using colloidal silica, and then etched with a 3 vol.% nitric acid ethanol solution to make the structure visible. Under the condition of an accelerating voltage of 15 kV, a SEM (Scanning Electron Microscope) is used to observe 10 fields of view at a magnification of 50 times at a position 10 mm below the surface of the slab, and the area ratio of ferrite in 10 fields of view is calculated using Adobe's PHOTOSHOP (registered trademark) for the obtained organizational image, and these values ​​are averaged to obtain the area ratio of ferrite. It should be noted that compared with other structures (pearlite, bainitic ferrite, tempered martensite, quenched martensite, and retained austenite), the particle size of ferrite is large, the surface is smooth, and the contrast is dark, so it can be easily distinguished at a magnification of 50 times.

[0123] [Method for determining the area ratio of bainitic ferrite, tempered martensite, quenched martensite, retained austenite and pearlite]

[0124] As for the method for measuring the area ratio of these structures, the structures are displayed on the observation surface of the slab in the same manner as the method for measuring ferrite described above. Under the condition of an accelerating voltage of 15 kV, SEM is used to exclude ferrite from the field of view at a position 10 mm below the surface of the slab, and 10 fields of view are observed at a magnification of 10,000 times. The area ratios of bainitic ferrite, tempered martensite, quenched martensite, retained austenite and pearlite in 10 fields of view are calculated from the obtained structure images using Adobe's PHOTOSHOP (registered trademark), and these values ​​are averaged and calculated together with the area ratio of ferrite measured by the above method so that the total is 100%, and the area ratio of each structure is obtained. Bainitic ferrite is a structure of concave parts, tempered martensite is a structure of concave parts and contains fine carbides, quenched martensite is a structure of convex parts and has fine concavo-convex parts inside the structure, retained austenite is a structure of convex parts and has a flat structure inside the structure, and pearlite is a structure of concave parts and contains lamellar carbides. It should be noted that for bainitic ferrite and tempered martensite, since the total area ratio of bainitic ferrite and tempered martensite is obtained, it is not necessary to be able to distinguish each other.

[0125] [Evaluation method of slab cracking]

[0126] The evaluation method for slab cracking is based on the penetrant flaw detection test specified in JIS Z 2343: 2017, and the presence or absence of cracks on the wide and narrow surfaces of the slab is evaluated. After applying the developer, the appearance of the penetrant is visually inspected to visually check for cracks and scratches on the surface.

[0127] [Evaluation method of surface defects of steel sheets]

[0128] The evaluation method of the surface defects of the steel sheet after hot rolling, cold rolling, annealing or plating is visually evaluated by appearance inspection. The steel sheet with no scale-like folding marks, streaks, or unplated coating over the entire length and width of the steel sheet is evaluated as "no" surface defects, and the steel sheet with some scale-like folding marks, streaks, or unplated coating is evaluated as "present" surface defects.

[0129] [Mechanical properties]

[0130] The method for measuring the mechanical properties (tensile strength TS) is as follows. In the tensile test, a JIS No. 5 test piece collected in a manner that the length of the tensile test piece is perpendicular to the rolling direction of the steel plate (C direction) is used, and TS (tensile strength) is measured in accordance with JIS Z2241:2011. It should be noted that in the present invention, a TS of 590 MPa or more is defined as high strength and evaluated as qualified.

[0131] (Example 1)

[0132] Table 1 shows the composition of the steel slabs used in the test. The steel slabs were cooled under the cooling conditions including reheating shown in Tables 2-1 and 2-2. In Tables 2-1 and 2-2, t1 is the residence time (s) at 1200°C to 1450°C at the center of the slab width and 10 mm below the surface, v1 is the average cooling rate (°C / hr) when the surface temperature at the center of the slab width is 700°C to 850°C, v2 is the average cooling rate (°C / hr) when the surface temperature is 550°C to 700°C, v3 is the average cooling rate (°C / hr) when the surface temperature is 400°C to 550°C, v4 is the average cooling rate (°C / hr) to the cooling stop temperature of 250°C to 400°C, Tf is the cooling stop temperature (°C), Th is the reheating temperature (°C), and v5 is the average cooling rate (°C / hr) when the surface temperature is 200°C to the reheating temperature. In addition, the "Cracking" column records the presence or absence of cracking during the cooling of the slab. d(γ) is the average prior austenite grain size (mm), BF+TM is the total area ratio of bainitic ferrite and tempered martensite (%), Rγ is the area ratio of retained austenite (%), F is the area ratio of ferrite (%), and P+FM is the total area ratio of pearlite and quenched martensite (%). For the steel slabs of the composition provided for the experiment, by setting appropriate cooling conditions including reheating, the prior austenite grain size and microstructure of the present invention can be satisfied, and no cracking is observed in the steel slabs. Under conditions deviating from the scope of the present invention, cracking is observed in the steel slabs.

[0133] [Table 1]

[0134]

[0135] [Table 2-1]

[0136]

[0137] [Table 2-2]

[0138]

[0139] (Example 2)

[0140] Tables 3-1 and 3-2 show the composition of the steel slabs used in the test. The steel slabs were cooled under the cooling conditions shown in Tables 4-1 and 4-2, where the temperature was uniformly reduced. In Tables 4-1 and 4-2, t1 is the residence time (s) at 1200°C to 1450°C at the center of the slab width and 10 mm below the surface, v1 is the average cooling rate (°C / hr) when the surface temperature at the center of the slab width is 700°C to 850°C, v2 is the average cooling rate (°C / hr) when the surface temperature is 550°C to 700°C, v3 is the average cooling rate (°C / hr) when the temperature is 400°C to 550°C, and v6 is the average cooling rate (°C / hr) when the temperature is 200°C to 400°C. In addition, the "Cracking" column shows the presence or absence of cracking during the cooling of the slab. d(γ) is the average prior austenite grain size (mm), BF+TM is the total area ratio of bainitic ferrite and tempered martensite (%), Rγ is the area ratio of retained austenite (%), F is the area ratio of ferrite (%), and P+FM is the total area ratio of pearlite and quenched martensite (%). For the steel slabs of the composition provided for the experiment, the prior austenite grain size and microstructure of the present invention can be satisfied by setting appropriate cooling conditions in which the temperature is uniformly lowered, and no cracks are found in the steel slabs. Under conditions deviating from the scope of the present invention, cracks are observed in the steel slabs.

[0141] [Table 3-1]

[0142]

[0143] [Table 3-2]

[0144]

[0145] [Table 4-1]

[0146]

[0147] [Table 4-2]

[0148]

[0149] Next, the cooled steel slab is hot rolled under the conditions described in Tables 5-1 and 5-2, and then subjected to cold rolling, annealing and plating. THs in Tables 5-1 and 5-2 is the slab heating temperature (°C), THf is the finish rolling end temperature of hot rolling (°C), and THr is the coiling temperature of the hot-rolled steel strip (°C). CR is the rolling ratio (%) of cold rolling, which indicates the percentage of the thickness of the plate after rolling relative to the thickness of the plate until rolling. TA is the annealing temperature of the cold-rolled steel sheet (°C), TW is the water quenching start temperature (°C), TAf is the cooling stop temperature after annealing (°C), and TAh is the subsequent reheating temperature (°C). CR in the variety column is a cold-rolled steel sheet, GI is a hot-dip galvanized steel sheet, GA is an alloyed hot-dip galvanized steel sheet, EG is an electrogalvanized steel sheet, Al is a hot-dip aluminum plated steel sheet, and HR is a hot-rolled steel sheet. When the steel slab according to the present invention in which no cracking was observed was hot rolled as a raw material, no surface defects were observed in the steel sheet, and a tensile strength (TS) of 590 MPa or more was achieved.

[0150] [Table 5-1]

[0151]

[0152] [Table 5-2]

[0153]

[0154] Industrial Applicability

[0155] By using the slab cooling method of the present invention, even a high-alloy slab with low toughness will not crack after casting, and the yield rate during manufacturing can be greatly improved. In addition, by using the slab for high-strength steel plate of the present invention, a high-strength hot-rolled steel plate, a high-strength cold-rolled steel plate, and a high-strength plated steel plate without surface defects can be obtained even for high alloys. When these steel plates are used in automobile suspension parts, structural parts, and frame parts, the reliability of the automobile can be ensured and the weight of the vehicle body can be reduced, so it is useful in industry.

Claims

1. A slab for a high-strength steel plate, which is a continuously cast slab for a high-strength steel plate, characterized in that: The average original austenite grain size at a position 10 mm away from the surface of the slab is less than 2.0 mm, and in the microstructure at a position 10 mm away from the surface of the slab, the total area ratio of bainitic ferrite and tempered martensite is more than 50% and less than 97%, the area ratio of retained austenite is more than 3% and less than 30%, the area ratio of ferrite is less than 20%, and the total area ratio of pearlite and quenched martensite is less than 20%.

2. The slab for high-strength steel sheet according to claim 1, wherein: The slab for high-strength steel sheet has the following composition, which contains, by mass %, C: 0.10% or more and 0.50% or less, Si: 0.10% to 2.50% Mn: 1.00% or more and 5.00% or less, P: 0.100% or less, S: 0.0200% or less, Al: 0.005% or more and 2.500% or less, N: 0.0100% or less and O: 0.0100% or less, Further optionally containing Ti: 0.200% or less, Nb: 0.200% or less, V: 0.200% or less, Ta: 0.10% or less, W: 0.10% or less, B: 0.0100% or less, Cr: 1.00% or less, Mo: 1.00% or less, Co: 1.00% or less, Ni: 1.00% or less, Cu: 1.00% or less, Sn: 0.200% or less, Sb: 0.200% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, REM: 0.0100% or less, Zr: 0.100% or less, Te: 0.100% or less, Hf: 0.10% or less and Bi: 0.200% or less At least one element selected from The balance is Fe and inevitable impurities.

3. The slab for high-strength steel sheet according to claim 1, wherein: The slab for high-strength steel sheet has the following composition, which contains, by mass %, C: 0.10% or more and 0.50% or less, Si: 0.70% to 2.50% Mn: 1.00% or more and 5.00% or less, P: 0.100% or less, S: 0.0200% or less, Al: 0.005% or more and 2.500% or less, N: 0.0100% or less and O: 0.0100% or less, Further optionally containing Ti: 0.200% or less, Nb: 0.200% or less, V: 0.200% or less, Ta: 0.10% or less, W: 0.10% or less, B: 0.0100% or less, Cr: 1.00% or less, Mo: 1.00% or less, Co: 1.00% or less, Ni: 1.00% or less, Cu: 1.00% or less, Sn: 0.200% or less, Sb: 0.200% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, REM: 0.0100% or less, Zr: 0.100% or less, Te: 0.100% or less, Hf: 0.10% or less and Bi: 0.200% or less At least one element selected from The balance is Fe and inevitable impurities.

4. A method for cooling a slab for a high-strength steel plate, characterized in that: The slab for high-strength steel sheet having the component composition described in claim 2 is cooled so that the residence time at 1200°C to 1450°C at the center of the slab width and 10 mm below the surface is 130 seconds or less, then cooled so that the average cooling rate when the surface temperature at the center of the slab width is 700°C to 850°C is 25°C / hr or more, then cooled so that the average cooling rate at 550°C to less than 700°C is 20°C / hr or more, then cooled so that the average cooling rate at 400°C to less than 550°C is 15°C / hr or more, then cooled to a cooling stop temperature of 250°C to less than 400°C so that the average cooling rate is 10°C / hr or more, then heated so as to reach a reheating temperature higher than the cooling stop temperature and less than 450°C, and then cooled so that the average cooling rate at 200°C to less than the reheating temperature is 30°C / hr or less.

5. A method for cooling a slab for a high-strength steel plate, characterized in that: The slab for high-strength steel plate having the component composition described in claim 3 is cooled in such a manner that the residence time at a temperature of 1200°C to 1450°C at the center of the slab width and 10 mm below the surface is 130 seconds or less, and then cooled in such a manner that the average cooling rate is 25°C / hr or more when the surface temperature at the center of the slab width is 700°C to 850°C, and then cooled in such a manner that the average cooling rate is 20°C / hr or more when the surface temperature is 550°C to 700°C, and then cooled in such a manner that the average cooling rate is 10°C / hr or more when the surface temperature is 400°C to 550°C, and then cooled in such a manner that the average cooling rate is 30°C / hr or less when the surface temperature is 200°C to 400°C.

6. A method for producing a high-strength hot-rolled steel sheet, characterized in that: The slab for high-strength steel sheet according to any one of claims 1 to 3 is heated in a manner such that the slab heating temperature is in the range of 1000°C to 1300°C, finish rolling is performed after rough rolling in a manner such that the finishing temperature of finish rolling is in a range of 750°C to 1000°C, and coiling is performed in a manner such that the coiling temperature is in a range of 750°C to 750°C.

7. A method for manufacturing a high-strength cold-rolled steel sheet, characterized in that: After pickling the high-strength hot-rolled steel sheet produced by the production method according to claim 6, cold rolling is performed so that the reduction ratio becomes 30% or more and 80% or less. Further, one treatment selected from the following treatments is optionally performed: a) heating the high-strength cold-rolled steel sheet obtained by the cold rolling so that the annealing temperature is 750° C. to 950° C., cooling to a cooling stop temperature of 300° C. to 600° C., and then cooling to 100° C. or less; b) heating the high-strength cold-rolled steel sheet obtained by the cold rolling so that the annealing temperature is 750° C. to 950° C., cooling to a cooling stop temperature of 130° C. to 400° C., then heating again to 200° C. to 450° C., and then cooling to 100° C. or less; and c) The high-strength cold-rolled steel sheet obtained by the cold rolling is heated so that the annealing temperature becomes 750°C to 950°C, water quenched at 500°C or higher, water-cooled to 100°C or lower, and then reheated at 100°C to 300°C.

8. A method for producing a high-strength plated steel sheet, characterized in that: The high-strength cold-rolled steel sheet obtained by cold rolling according to claim 7 is heated so that the annealing temperature becomes 750° C. or higher and 950° C. or lower, and then the high-strength cold-rolled steel sheet is subjected to a molten metal plating treatment to obtain a plated steel sheet, and then the plated steel sheet is cooled under the condition that the cooling stop temperature is 150° C. or lower, Optionally, the molten metal plating treatment is one selected from zinc plating, zinc-based alloy plating, zinc-Al alloy plating, and Al plating.

9. The method for producing a high-strength plated steel sheet according to claim 8, wherein: The plated steel sheet subjected to the hot-dip metal plating treatment is subjected to an alloying treatment.

10. A method for producing a high-strength plated steel sheet, characterized in that: Using the high-strength cold-rolled steel sheet manufactured by the manufacturing method according to claim 7, performing electroplating treatment on the surface, Optionally, the electroplating treatment is performed by one selected from the group consisting of zinc plating, zinc-based alloy plating, zinc-Al alloy plating, and Al plating.